ВИМІРЮВАННЯ ТА КОМПЕНСАЦІЯ НЕАКТИВНИХ ПОТУЖНОСТЕЙ ТРИФАЗНИХ СИСТЕМ ЕЛЕКТРОЖИВЛЕННЯ ЗАСОБАМИ ПАРАЛЕЛЬНОЇ АКТИВНОЇ ФІЛЬТРАЦІЇ - Артеменко, М.Ю.; Кутафін, Ю.В.; Чопик, В.В.; Михальський, В.М.; Шаповал, І.А.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2024)
In this paper, the power theory of three-phase power supply systems was further developed by substantiating new formulas for calculating the unbalance power of three-phase four-wire power supply systems based on the measurement of active and reactive powers of individual phases, which can be used to form compensation signals in distributed active filtering with centralized control. A new structural scheme for controlling an autonomous shunt active filter with extended functionality and increased speed is proposed, which can be used in both three-wire and four-wire power supply systems. Computer modeling confirmed the adequacy of the new formulas for calculating the unbalance power components and the effectiveness of the proposed active filtering strategies to minimize power losses in the transmission line. References 11, figures 3, table 1.